RISIKO PENYEBAB TERJADINYA HIPERTENSI DI DESA BUNGA PUTIH KECAMATAN MARANGKAYU KABUPATEN KUTAI KARTANEGARA - Muhammad Rizky Permana (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2017)
Results Health Research shows Kalimantan Timur Indonesia was ranked third in Indonesia in the amount of the highest prevalence of hypertension of 29.9%.Data from the health center in 2013 Marangkayu hypertension increased by 21% to 35% in 2015.This study aims to determine the cause of the risk of hypertension in the village of White Flower Marangkayu District of Kutai regency in 2016. The study design used is case control study.The sample in this study were 80 people.The dependent variable studied is hypertension, independent variables studied were Sodium, Fat, Fruit and Vegetable Consumption, Water, Physical Activity, Smoking and Stress with data analysis and the Spearman rank test OR. Concluded associated with hypertension are sodium (p = 0.039 and OR = 2.636), physical activity (p = 0.034 and OR = 2.816), smoking (p = 0.025 and OR = 2.810), and stress (p = 0.045 and OR = 2,500 ).And unrelated is fat (p = 0.816 and OR = 1.118), fruits and vegetables (p = 0.346 and OR = 0.632), and water (p = 0.505 and OR = 0.630). Based on these results concluded that sodium, physical activity, smoking and stress are risk factors associated with hypertension.While the consumption of fats, fruits and vegetables, and water is not a factor associated with hypertension.Suggested to White Flower villagers to change their healthy lifestyle like berolahrga, reduce the consumption of salty foods and cholesterol, not smoking, and reducing stress.